GAMBARAN GANGGUAN PENDENGARAN PADA PASIEN OTITIS MEDIA SUPURATIF KRONIS DI POLIKLINIK THT-KL RSUP SANGLAH TAHUN 2013 - Ni Luh Putu Diaswari Predani; Komang Andi Dwi Saputra (E-Jurnal Medika Udayana, 2017)
Hearing loss is one of the most significant health problem which associated with many enduring difficulties. This study was conducted to determine hearing loss in CSOM patients, identify CSOM type and hearing loss description in CSOM patients. This study was carried out by using audiometric test from Audiology Division in ENT Policlinic Sanglah Hospital in 2013. The study material is audiometric test result by its sex characteristic, age, CSOM type, type of hearing loss and degree of hearing loss. Of 46 patients we found 62 ears of CSOM cases. The study result found 56.5% patients was female, 28.3% within age 31-40 years and benign type of CSOM 87.1%. The main results show: hearing description in CSOM patient are 16.1% with normal hearing and 83.9% with hearing loss; the most type of hearing loss is mild conductive hearing loss. Thus, it is concluded that hearing loss is often seen in CSOM patients. The result of this study could be applied to find more relation of hearing loss in CSOM patients. Keywords: chronic suppurative otitis media, hearing loss